FR1.1: Doing GREAT: Genesis and evolution of a gender training program for agricultural researchers - Mangheni, Margaret Najjingo (Makerere University, 2022)
Women play a critical role in agriculture especially in developing countries despite gender-based constraints which limit their contribution. Women's empowerment has been strongly linked to achievement of development outcomes thus gaining precedence in global development discussion. While several studies have investigated the notions of empowerment, masculinities and social/gender norms, these thematic areas have been studied in isolation regardless of their linkages. For example, evidence indicates that masculinities and social norms are anchored in social cultural contexts, and are thus bound to vary in different agricultural systems. How do these themes intersect? Using a mixed methods approach, we interrogated the interconnection of women's empowerment, masculinities and social norms, and how these influence household food security and women's income. Qualitative case studies helped understand local constructions of masculinities and femininities, women's empowerment; and how these in turn influence development outcomes. The findings on masculinities and women empowerment are presented by Businge et al., ; femininities and women's economic empowerment by Shimali et al., and, community perception of women's empowerment by Nakyewa et al., (all submitted for this conference). A quantitative survey (to be conducted in July-August 2022) will be used to measure the level and drivers of women's empowerment and project outcomes as well as household food security and women's income using Pro-WEAI with an add-on masculinities module. This paper will present a synthesis of the qualitative and quantitative evidence around the interconnections between women empowerment, masculinities, household food security and women's income.